GAMBARAN ULTRASONOGRAFI GINJAL PADA PENDERITA NEFROLITIASIS DIBAGIAN RADIOLOGI FK UNSRAT BLU RSUP PROF. DR. R. D. KANDOU MANADO PERIODE 1 JANUARI – 30 JUNI 2014 - Ridwan, Moch. Syafrudin; Timban, Joan F. J.; Ali, Ramli Hadji (Universitas Sam Ratulangi, 2015)
Abstract: Nephrolithiasis is a disease which the symptom is indicated by the existence of a single or more solid mass of hard material like a stone which is found in the kidney tubule, calyx, infundibulum, kidney pelvis, and the whole of kidney calyx of the sufferer. Mostly, the doctors use imaging like ultrasonography to checkup the patients’ condition in order to ascertain the diagnosis of nephrolithiasis. Ultrasonography can give the spesific image if there is any stone located in the kidney. As a result, doctors will get some easiness in determining the patients diagnosis. The objective of this research is to figure out the kidney image resulted from ultrasonography of nephrolithiasis sufferers in Radiology Division, Medical Faculty, Samratulangi University/ Faculty Students Senate of Radiology, Public Service Corporation of Prof. Dr. R. D. Kandou Hospital, Manado, In the period of January 1st – June 30th 2014.The researcher used descriptive retrospective as the research method. By using medical notes found in Radiology Division, Public Service Corpration of Prof. Dr. R. D. Kandou Hospital, Manado, In the period of January 1st – June 30th 2014 as secondary data. Conclusion:The researcher then found that there were 105 cases of nephrolithiasis from totally result of kidney ultrasonography to the sufferers of nephrolithiasis. Many of the suferrers were men (62,9%) in average ages from 56 to 65 years old (36,2%). According to the location, kidney stone were found mostly in bilateral nepholithiasis (37,1%). The resercher also figured out that most of nephrolithiasis sufferers had a complication with chronic kidney disease (39,0%) and complication with hidronephrosis (19,0%). The patients who complain about pain on their weists should have kidney ultrasonography test to help the doctor to diagnose the causes, to avoid the possibity of another abnormal organ, and prevent the serious nephrolithiasis causes.Keywords: kidney ultrasonography, nephrolithiasisAbstrak: Nefrolitiasis merupakan suatu penyakit dengan gejala ditemukannya satu atau beberapa massa keras seperti batu yang terdapat di dalam tubuli ginjal, kaliks, infundibulum, pelvis ginjal, serta seluruh kaliks ginjal. Pemeriksaan yang sering digunakan dalam penegakan diagnosis nefrolitiasis adalah pemeriksaan imaging salah satunya adalah Ultrasonografi.Ultrasonografi dapat memberikan gambaran yang jelas apabila terdapat batu yang berlokasi di ginjal. Sehingga mempermudah dokter untuk menentukan diagnosis pasien. Tujuan penelitian ini untuk mengetahui gambaran hasil Ultrasonografi ginjal pada penderita Nefrolitiasis di Bagian Radiologi FK UNSRAT/SMF Radiologi BLU RSUP Prof. Dr. R. D. Kandou Manado Periode 1 Januari – 30 Juni 2014.Penelitian ini merupakan penelitian deskriptif retrospektif dengan memanfaatkan data sekunder berupa catatan medik yang terdapat di Bagian Radiologi BLU RSUP Prof. Dr. R. D. Kandou Manado Periode 1 Januari – 30 Juni 2014. Simpulan:Keseluruhan hasil Ultrasonografi ginjal pada penderita Nefrolitiasis ditemukan 105 kasus nefrolitiasis, dengan penderita nefrolitiasis lebih banyak terjadi padalaki-laki(62,9%).Penderita nefrolitiasis terbanyak pada kelompok umur 56 – 65 tahun (36,2%).Penderita nefrolitiasis berdasarkan letak batu yaitu nefrolitiasis bilateral (37,1%).Penderita nefrolitiasis dengan komplikasi CKD yaitus ebanyak (39,0%).Penderita nefrolitiasis dengan komplikasi Hidronefrosis yaitu sebanyak (19,0%). Penderita yang datang dengan keluhan rasa nyeri pada daerah pinggang sebaiknya dipastikan penyebabnya melalui pemeriksaan Ultrasonografi ginjal untuk membantu mendiagnosis, menyingkirkan kemungkinan kelainan pada daerah organ lainnya dan mencegah memberatnya penyebab nefrolitiasis.Kata kunci: ultrasonografi ginjal, nefrolitiasis